A Comprehensive Review of Power Quality Issues and Measurement for Grid-Integrated Wind Turbines - Zobaa, Ahmed F.; Ahmed, Ibrahim; Abdel Aleem, Shady H.E. (Recent Advances in Electrical & Electronic Engineering, 2019)
Background: Renewable energy generation using wind energy has emerged worldwide and has opened up significant new markets in electrical power generation. However, different factors that affect power quality performance of Wind Turbine (WT) applications such as wind speed fluctuation and use of power electronic based devices have been presented due to the rapid increase of WT installations. Methods: Accordingly, it is worth to measure, assess and evaluate the quality of the generated power of these WTs in order to ensure their compliance with the grid-integration conditions. In this work, first, a general classification of WTs and their operating principle is reviewed. Because variable speed WTs are frequently used in today’s power systems, much attention was paid to this type of turbines. Second, the various power quality aspects caused due to the integration of the wind energy systems into the grid were presented and discussed. Flickers, harmonic distortion, response to voltage dip, active power, and reactive power requirements, fault-ride through and short-circuit current contribution were the addressed power quality problems. Results: Further, the study pointed out the need for a unified evaluation process to assess the power quality performance of the grid-connected wind systems. Conclusion: Also, it was concluded that success in integrating more wind energy systems hinges on accurate power quality performance assessment.
Keywords: power quality